1995
DOI: 10.1016/0735-1097(95)00123-h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged catecholamine infusion on immunoregulatory function: Implications in congestive heart failure

Abstract: The results of our study indicate that prolonged elevation of catecholamine levels alters immune cell proliferation and differentiation. These alterations differ greatly from those induced by short-term stimulation but, for the most part, parallel those found in patients with congestive heart failure. We postulate that the shifts in immunoregulatory cell type and function seen in patients with congestive heart failure are due, in part, to longstanding increases in circulating catecholamine levels and may play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Also, corticosteroids and catecholamine-induced increased accumulation of lymphocytes in the spleen, lymph nodes and mucosal sites which decrease in lymphocytes in the blood (Viswanathan and Dhabhar, 2005). In contrast, some studies have shown that stress increased blood WBCs numbers in rats (Harris et al, 1995) and humans (Bosch et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Also, corticosteroids and catecholamine-induced increased accumulation of lymphocytes in the spleen, lymph nodes and mucosal sites which decrease in lymphocytes in the blood (Viswanathan and Dhabhar, 2005). In contrast, some studies have shown that stress increased blood WBCs numbers in rats (Harris et al, 1995) and humans (Bosch et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…4A,B). Since elevated concentrations of catecholamines can trigger lymphocyte cell death (Harris et al, 1995;Gu et al, 2000;Stevenson et al, 2001;Wahle et al, 2002;del Rey et al, 2003), we tested whether the reduction in spleen size and splenocyte number after T3 SCI was a result of increased immune cell apoptosis. Western blot analyses of homogenized spleen showed elevated levels of activated caspase-3 (a primary effecter of apoptosis) only after T3 SCI; thereby confirming our initial hypothesis (p<0.05; Fig.…”
Section: T3 Sci Induces Splenocyte Cell Death and B Cell Apoptosismentioning
confidence: 99%
“…This deficit is overcome by activating B cells in the presence of β2-adrenergic receptor (β2AR) agonists (e.g., terbutaline) (Podojil and Sanders, 2003). However, repeated or prolonged exposure of B cells to NE or other β2AR agonists is immunosuppressive (Melmon et al, 1974;Keller et al, 1983;Maisel, 1994;Harris et al, 1995;Woiciechowsky et al, 1998;Prass et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, infusion of catecholamines in pharmacological doses was found to evoke a transient leukocytosis [2,3] in a biphasic manner: within the initial 30 minutes, predominantly lymphocytes are mobilized, while later on an increased number of granulocytes was conspicuous in the peripheral blood stream [3]. Upon physiological stimuli, like acute psychological stress [1], lymphocyte subpopulations, particularly natural killer cells [1,5], expand, most probably due to adrenergic mechanisms, since betablockers can prevent these alterations in lymphocyte subsets. The lymphocytic adrenoceptors moreover are subject to dynamic regulation by their agonists [6], indicative of functional feedback loops.…”
Section: Schlüsselwörter: Herzinsuffizienz · Katecholamine · Zytokinementioning
confidence: 99%